Eugene Schuyler papers - Schuyler, Eugene, 1840-1890.
Letterpress copies of correspondence and writings relating to Schuyler's activities (1873-1876) as secretary of the American legation in Saint Petersburg, to his service (1876-1878) as consul and secretary of the American legation in Constantinople, and to his book, Turkistan: Notes of a Journey in Russian Turkestan, Khokand, Bukhara, and Kuldja (1876). Subjects in the correspondence include matters relating to the decline of the Ottoman Empire, advance of Russia into central Asia, Balkan question, Treaty of Berlin (1878), publication of his book, personal matters, and financial affairs. Correspondents include Hamilton Fish, Marshall Jewell, Frederick William Seward, and Henry Yale.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
Diplomat, scholar, and author.
Keywords: Fish, Hamilton, -- 1808-1893 -- Correspondence; Jewell, Marshall, -- 1825-1883 -- Correspondence; Seward, Frederick William, -- 1830-1915 -- Correspondence; Yale, Henry -- Correspondence; Treaty of Berlin -- (1878); Eastern question (Balkan); Russians -- Central Asia; Istanbul (Turkey) -- History; Russia -- Description and travel; Russia -- Foreign relations -- United States; Russia -- History -- Alexander II, 1855-1881.; Saint Petersburg (Russia) -- History; Turkey -- Foreign relations -- United States; Turkey -- History -- Ottoman Empire, 1288-1918.; Diplomatic and consular service, American -- Russia; Diplomatic and consular service, American -- Turkey; United States -- Foreign relations -- 1865-1898.; United States -- Foreign relations -- Russia; United States -- Foreign relations -- Turkey; Asia, Central -- History; Authors; Diplomats; Scholars